Fa’āliyatu Istikhdam Word Wall Kā Washilah al-Taqwim li al-Tarqiyati Natāij al- Ta’allum Fi al-Mahārah al-Qirā’ah - Hubbabah; Khoirotun Ni’mah; Ida Latifatul Umroh (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
This study aims to determine the effectiveness of using Wordwall as an evaluation tool in Arabic reading skills (maharah qira’ah) among tenth-grade students at MA-K PKPPS Roudlotul Mutaallimin Wonosalam Lamongan. The research employed a quantitative approach with a quasi-experimental design involving two groups: an experimental group and a control group. Data were collected through pre-tests, post-tests, observations, questionnaires, and interviews. The findings revealed a significant improvement in the experimental group’s learning outcomes after using Wordwall. The mean post-test score of the experimental group reached 75.00, while the control group achieved only 57.67. Statistical tests (paired and independent t-tests) showed a significance value of less than 0.05, indicating a significant impact of Wordwall on students’ learning outcomes. Additionally, observations and questionnaires indicated that Wordwall is attractive, easy to use, increases student participation, and enhances learning motivation. Therefore, Wordwall is proven effective as a learning outcomes media in teaching maharah qira’ah.